Endothelium-Dependent Relaxation Effect of Apocynum venetum Leaf Extract via Src/PI3K/Akt Signalling Pathway - Lau, Yeh Siang (MDPI, 2015)
Botanical herbs are consumed globally not only as an essential diet but also as medicines or as functional/recreational food supplements. The extract of the Apocynum venetum leaves (AVLE), also known as Luobuma, exerts its antihypertensive effect via dilating the blood vessels in an endothelium- and concentration-dependent manner with optimal effect seen at as low as 10 µg/mL. A commercial Luoboma “antihypertensive tea” is available commercially in the western province of China. The present study seeks to investigate the underlying cellular mechanisms of the nitric oxide (NO)-releasing property of AVLE in rat aortas and human umbilical vein endothelial cells (HUVECs). Endothelium-dependent relaxation induced by AVLE was assessed in organ chambers in the presence or absence of polyethyleneglycol catalase (PP2, 20 µM; inhibitor of Src kinase), wortmannin (30 nM) and LY294002 (20 µM; PI3 (phosphatidylinositol3)-Kinase inhibitor), NG-nitro-l-arginine (L-NAME, 100 µM; endothelial NO synthase inhibitor (eNOS)) and ODQ (1 µM; soluble guanylyl cyclase inhibitor). Total nitrite and nitrate (NOx) level and protein expression of p-Akt and p-eNOS were measured. AVLE-induced endothelium-dependent relaxation was reduced by PP2, wortmannin and LY294002 and abolished by L-NAME and ODQ. AVLE significantly increased total NOx level in rat aortas and in HUVECs compared to control. It also instigated phosphorylation of Akt and eNOS in cultured HUVECs in a concentration-dependent manner and this was markedly suppressed by PP2, wortmannin and LY294002. AVLE also inhibited superoxide generated from both NADPH oxidase and xanthine/xanthine oxidase system. Taken together, AVLE causes endothelium-dependent NO mediated relaxations of rat aortas through Src/PI3K/Akt dependent NO signalling pathway and possesses superoxide scavenging activity.